Time and Vision in Ben Okri’s The Famished Road - Teimouri, Mahdi (SARE: Southeast Asian Review of English, 2017)
The Famished Road, which won the Man Booker Prize for Ben Okri in 1991, is the story of an abiku child named Azaro born to a destitute Nigerian family in an unknown village somewhere in Nigeria. The time of political turmoil, fervor and agitation, can be estimated to be in the wake of Independence. According to Nigerian mythology, an abiku is a spirit child who commutes between the worlds of the living and of spirits. He or she is born repeatedly to the same parents. We are told at the beginning of the story that the abiku child has made up his mind to end this repeated reincarnation and stay in the world of the living. He enumerates different reasons such as being fed up with the coming and going, the wish to savor this world, to enjoy ’the sublime mood of eternity’ and finally the face of his mother: ’I wanted to make happy the bruised face of that woman who would become my mother’ (5). Ironically, his stay brings no happiness and comfort to his parents and he becomes a burden, adding to the chagrin of a penurious livelihood.